Rising wages: Has China lost its global labor advantage? - Dennis Tao Yang; Vivian Chen; Ryan Monarch (Institute for the Study of Labor (IZA), 2010)
We document dramatic rising wages in China for the period 1978-2007 based on multiple sources of aggregate statistics. Although real wages increased seven-fold during the period, growth was uneven across ownership types, industries and regions. Since the late 1990s, the wages of state-owned enterprises have increased rapidly and wage disparities between skill-intensive and labor-intensive industries have widened. Comparisons of international data show that China's manufacturing wage has already converged to that of Asian emerging markets, but China still enjoys enormous labor cost advantages over its neighboring developed economies. Our analysis suggests that China's wage growth will stabilize to a moderate pace in the near future.
Keywords: J31; J21; O5; 330; Wage growth; aggregate statistics; China; international comparison; Lohnniveau; Wirtschaftswachstum; Lohnstruktur; Komparativer Kostenvorteil; Industrielohn; Internationaler Wettbewerb; China; Industriestaaten; Schwellenländer